RHS Wisley Experts Gardeners' Advice (Royal Horticultural Society) - Editor-in-chief Alan Toogood (London Dorling Kindersley, 2004)
Practical advice for gardeners from the acknowledged experts at RHS Wisley. They tackle over 300 common gardening problems, from which plants to grow to dealing with pests.
Includes Colored Illustraions Index
Keywords: Gardening